Differences in human antibody reactivity to Plasmodium falciparum variant surface antigens are dependent on age and malaria transmission intensity in northeastern Tanzania - Vestergaard, L.S.; Lusingu, J.P.; Nielsen, M.A.; Mmbando, B.P.; Dodoo, D.; Akanmori, B.D.; Alifrangis, M.; Bygbjerg, I.C.; Lemnge, M.M.; Staalsoe, T.; Hviid, L.; Theander, T.G. (Infection and Immunity 76(6): 2706-14, 2008)
Plasmodium falciparum variant surface antigens (VSA) are involved in the pathogenesis of malaria. Immunoglobulin G (IgG) with specificity for VSA (anti-VSA IgG) is therefore considered important for acquired immunity. To better understand the nature and dynamics of variant-specific IgG responses at population level, we conducted an immunoepidemiological study in nearby communities in northeastern Tanzania, situated at different altitudes and therefore exposed to different levels of P. falciparum transmission intensity. Samples of plasma and infected red blood cells (IRBC) were collected from 759 individuals aged 0 to 19 years. Plasma levels of IgG with specificity for VSA expressed by a panel of different parasite isolates were measured by flow cytometry, while the ability of plasma to inhibit IRBC adhesion to CD36 was examined in cellular assays. The level and repertoire of the heterologous anti-VSA IgG response developed dramatically in individuals at 1 to 2 years of age in the high-transmission area, reaching a maximum level at around 10 years of age; only a modest further increase was observed among older children and adults. In contrast, at lower levels of malaria transmission, anti-VSA IgG levels were lower and the repertoire was more narrow, and similar age- and transmission-dependent differences were observed with regard to the ability of the plasma samples to inhibit adhesion of IRBC to CD36. These differences indicate a strong and dynamic relationship between malaria exposure and functional characteristics of the variant-specific antibody response, which is likely to be important for protection against malaria.